Identification of Groundwater Aquifers Using Geoelectric Methods with Schlumberger Configuration in Peatland Areas, West Kalimantan, Indonesia - Rasmi Rasmi; Yuris Sutanto; Radhitya Perdhana; Muliadi Muliadi; Muhardi Muhardi; Mahmuddin Marbun; Amir Machmud; Elok Surya Pratiwi (International Journal of Hydrological and Environmental for Sustainability, 2024)
The geoelectric-resistivity method with Schlumberger configuration is commonly used for groundwater exploration. This method helps identify changes in the resistivity of rock layers beneath the Earth's surface by flowing direct current (DC). In this research, geoelectric-resistivity was used to search for the existence of groundwater aquifers in water crisis areas with peat soil structures. In addition, this research aims to determine the depth of the aquifer layer based on resistivity values below the surface and  to identify variations in resistivity values below the surface. The method used in this research was the Schlumberger configuration resistivity geoelectric method with 4 measurement points, each with  a stretch length of 500 m . The research results show that the subsurface resistivity value in the Parit Haji Muksin II area is 2.69 Ohm m to 264 Ohm m. The unconfined aquifer at the research location was found at point 1 and point 2 at a depth of 3.94 m to 35.5 m, while the confined aquifer was found at points 3 and 4 at a depth of 13.6 m to 61.8 m. This study indicates the presence of potential groundwater resources in tropical peatlands, highlighting the necessity for further comprehensive research to ensure their sustainable utilization in the future.